Selective interfacial localization in conducting polycaprolactam/ethylene vinyl acetate/carbon black composites. Issue 6 (2nd May 2013) - Sinha, S.K.; Dubey, K.A.; Grover, V.; Sastry, P.; Bhardwaj, Y.K.; Panicker, L.; Tyagi, A.K.; Mahanwar, P.A.; Bambole, V.A.
<x xml:space="preserve">Abstract</x> Unusual electrical conductivity was demonstrated by ethylene vinyl acetate/polycaprolactam/carbon black (CB) composites. The critical exponent value was 1.2 ± 0.2 for ternary composites and was greater than 2.0 for the binary composites, indicating two‐dimensional electrical conduction in ternary composites. The ternary composites also showed inverted U‐shaped conductivity curves when CB weight fraction was greater than 10 wt%. However, at 10 wt% CB, a discontinuous conductivity curve showing conductivity only when polycaprolactam content was greater than 50% was observed, suggesting substantial variation in the interfacial characteristics with the change in the blend composition. Small‐angle X‐ray scattering studies pointed out that ternary composites can be viewed as a two‐phase system with sharp boundaries, and that interface layer in the composites does not exist. Differential scanning calorimetry studies suggested composition dependent variation in the crystallinity of polycaprolactam phase, partially contributing to the increase in the composites' conductivity at higher polycaprolactam fractions. POLYM. COMPOS., 34:912–919, 2013. © 2013 Society of Plastics Engineers